Developing Story Card Media to Enhance Narrative Writing Skills in Third-Grade Indonesian Language Learning - Aulia Khairani Harahap; Zaini Dahlan (Journal of Social Work and Science Education, 2027)
This study aimed to develop and evaluate story card media for narrative writing instruction in Indonesian language learning for third-grade elementary students, addressing difficulties in generating ideas, organizing events coherently, and expressing thoughts in written form. A Research and Development design with the ADDIE model was employed, involving 23 third-grade students at SD Negeri 101770 Tembung. Data were collected through classroom observation, teacher interviews, expert validation, response questionnaires, and pretest-posttest narrative writing assessments. Expert evaluations yielded feasibility scores of 90% (media), 94% (content), and 91% (language). Teacher and student response scores reached 92% and 90%, respectively, indicating high practicality. The class-level writing score increased from 40% (pretest) to 90% (posttest), with an N-gain of 0.83, categorized as high. This study offers a structured combination of visual sequences and contextual prompts specifically designed for third-grade learners' concrete operational characteristics, an underexplored intervention in Indonesian elementary narrative writing instruction. Teachers can use the cards as a low-complexity scaffold for collaborative planning and individual writing, providing an accessible, ready-to-implement instructional tool. This research contributes a feasible, practical, and effective story card medium for enhancing narrative writing skills, offering preliminary evidence for curriculum developers and educators seeking innovative, visually mediated approaches to literacy instruction in elementary classrooms.